2011
DOI: 10.1016/j.joen.2010.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Endotoxin Levels in Previous Studies on Primary Endodontic Infections

Abstract: This study has revealed that quantitative kinetic-turbidimetric and kinetic-chromogenic LAL methods are best fitted for the analysis of endotoxins in root canal infection, both being more precise and allowing better reproducibility compared with the endpoint-QCL assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 31 publications
2
44
0
2
Order By: Relevance
“…Six of these patients had high endotoxin levels in the first sampling (S1), in agreement with studies showing a correlation between clinical signs and symptoms and higher endotoxin levels (16,18,21,25). However, endotoxin levels were not elevated in the other 2 patients reporting pain.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Six of these patients had high endotoxin levels in the first sampling (S1), in agreement with studies showing a correlation between clinical signs and symptoms and higher endotoxin levels (16,18,21,25). However, endotoxin levels were not elevated in the other 2 patients reporting pain.…”
Section: Discussionsupporting
confidence: 87%
“…A positive correlation between endotoxin concentration in the root canal and the presence of endodontic signs and symptoms has been shown (16). Endotoxins have been detected in 100% of first samplings of root canals with necrotic pulp, with levels significantly higher in symptomatic teeth (17)(18)(19)(20)(21). Therefore, treatment of infected root canals should not only destroy bacteria but should also inactivate their endotoxins and other toxic products.…”
mentioning
confidence: 99%
“…Endo et al [7] investigating the levels of endotoxins in endodontically treated teeth, revealed a median value of 3.96 EU/mL by the Turbidimetric Kinetic LAL assay. Such difference might be attributed the LAL test selection [30]. Particularly, the KQCL-test (Kinetic Chromogenic LAL test) used in the present study is one of the LAL tests that best fits for analysis of endotoxins present in root canal infection because of its better precision and better reproducibility compared to other tests [30].…”
Section: Discussionmentioning
confidence: 95%
“…Such difference might be attributed the LAL test selection [30]. Particularly, the KQCL-test (Kinetic Chromogenic LAL test) used in the present study is one of the LAL tests that best fits for analysis of endotoxins present in root canal infection because of its better precision and better reproducibility compared to other tests [30]. After chemomechanical preparation (s2), both single-file reciprocating systems and rotary systems were effective in reducing more than 93 % of endotoxin contents from endodontically treated teeth, with no statistical differences between them.…”
Section: Discussionmentioning
confidence: 99%
“…All LAL reagents, endotoxin-free water, endotoxin-free pipette tips, endotoxin-free test tube, and endotoxin-free microplates were purchased from PBI International (Milan, Italy). Total endotoxin was measured using a kinetic chromogenic LAL test (Associates of Cape Cod Inc.) according to the manufacturer's instructions [11]. Briefly, a standard curve was plotted by using different concentrations (0.005, 0.05, 0.5, 5 and 50 EU/ml) of control standard endotoxin (CSE, E. coli 0113:H10).…”
Section: Analysis Of the Concentration Of Endotoxins Using The Limulumentioning
confidence: 99%